Modal Kultural Masyarakat di Daerah Rawan Bencana di Indonesia: Kajian Berdasarkan Karakteristik Wilayah - Hammada, Mortaza A Syafinuddin; Sampean, Sampean (Faculty of Humanities, Diponegoro University, 2024)
This research aims to explain the existence of cultural capital and its role in strengthening disaster resilience in various regions of Indonesia as a country that often faces natural disasters such as earthquakes, tsunamis, and volcanic eruptions. This research also aims to assess cultural traditions and practices in efforts to increase preparedness and response to natural disasters in various communities. This research uses a qualitative approach. Data was collected through observations and interviews in areas prone to natural disasters using Bourdieu's social capital analysis framework. This research uses purposive sampling to identify representative communities where cultural responses to natural disasters can be observed and documented. Primary data was taken through observation and direct involvement with the communities to understand the use of cultural knowledge in dealing with disasters. The results of this research show that communities rich in cultural heritage have stronger resilience and proactive disaster management behavior, utilizing historical wisdom and more advanced communal practices to mitigate the impact of disasters. Communities with less prominent cultural capital tend to experience greater difficulties, although they are gradually developing new cultural mechanisms to overcome the threat of natural disasters. The conclusion of this research shows that cultural capital is an important factor in efforts to strengthen community resilience to natural disasters. Efforts to integrate cultural insights into national natural disaster management policies and practices are very necessary. This integration not only preserves cultural heritage but also strategically increases response efficacy and disaster preparedness.